Pengembangan Media Pembelajaran PAK Berbasis Android (MPBA) Kelas X SMA Negeri 2 Tarutung - Christofer Samosir; Elsina Sihombing; Liyus Waruwu (Jurnal Euangelion, 2022)
Abstract: The purpose of this study was to determine whether the MPBA developed was feasible to use. This research is research and development that is used to develop or validate products used in learning. The development model used by the researcher is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model which was modified by the researcher according to the needs to become ADDIED (Analysis, Planning, Design, Development, Implementation, Evaluation, Dissemination). The subjects of this research are one material expert, one media expert, one PAK subject teacher. The feasibility test can be observed in the questionnaire results obtained from testing by material experts with 21 indicators and 4 aspects, then the total score is 81 from a maximum score of 84 in the "very feasible" category with a feasibility percentage of 96.42% from the range X> 81%, testing with one media expert with 29 indicators and 4 aspects, then obtained a total score of 113 out of a maximum score of 116 in the "very feasible" category with a feasibility percentage of 97.41% from the range X > 81%, testing with one PAK subject teacher with 50 indicators and 4 aspects, then obtained a total score of 172 from a maximum score of 200 in the "very feasible" category with a feasibility percentage of 86% from the range X > 81%. Based on the description above, it can be concluded that the Android-based PAK learning media developed with the ADDIED model (Analysis, Planning, Design, Development, Implementation, Evaluation, Dissemination) is considered "very feasible" to be used in learning. Keywords: development; instructional media; android-based     Abstrak: Tujuan penelitian ini adalah untuk mengetahui apakah MPBA yang dikembangkan layak untuk digunakan. Penelitian ini merupakan penelitian pengembangan (Research and Development) yang digunakan untuk mengembangkan atau memvalidasi produk yang digunakan dalam pembelajaran. Model pengembangan yang digunakan oleh peneliti adalah model ADDIE (Analysis, Design, Development, Implementation, Evaluation) yang dimodifikasi oleh peneliti sesuai dengan kebutuhan menjadi ADDIED (Analysis, Planning, Design, Development, Implementation, Evaluation, Dissemination). Subjek penelitian ini adalah satu orang ahli materi, satu orang ahli media, satu orang guru mata pelajaran PAK. Uji kelayakan dapat diamati pada perolehan hasil angket dari pengujian oleh ahli materi dengan 21 indikator dan 4 aspek, maka diperoleh jumlah skor 81 dari skor maksimum 84 dengan kategori “sangat layak” dengan persentase kelayakan 96,42% dari rentang X > 81%, pengujian dengan satu orang ahli media dengan 29 indikator dan 4 aspek, maka diperoleh jumlah skor 113 dari skor maksimum 116 dengan kategori “sangat layak” dengan persentase kelayakan 97,41% dari rentang X > 81%, pengujian dengan satu orang guru mata pelajaran PAK dengan 50 indikator dan 4 aspek, maka diperoleh jumlah skor 172 dari skor maksimum 200 dengan kategori “sangat layak” dengan persentase kelayakan 86% dari rentang X > 81%. Berdasarkan uraian di atas maka dapat disimpulkan bahwa media pembelajaran PAK berbasis android yang dikembangkan dengan model ADDIED (Analysis, Planning, Design, Development, Implementation, Evaluation, Dissemination) dinilai “sangat layak” untuk digunakan dalam pembelajaran. Kata Kunci: pengembangan; media pembelajaran; berbasis-android